The Development of the Problem Solving Framework in Managing Unregistered Drugs: Pharmacists Perspectives - Zulkifli, Nur Wahida; Abd Aziz, Noorizan; Hassan, Yahaya; Azmi Hassali, Mohamed; Zainal Bahrin, Nur Liyana (Journal of Pharmacy Practice and Community Medicine)
Background: Unregistered drug is one of the main important issues in Malaysia and is being taken very vigorously by the Malaysian Ministry of Health (MOH). However, the performance of the Pharmacy Enforcement Division amazingly increased but the problem still remains. Objective: The objective is to develop the problem solving framework by exploring the pharmacist perceptive on unregistered drugs. Methods: This study took place in pharmacist practice (hospital, community pharmacy and enforcement pharmacy unit) in Klang Valley. Sixteen pharmacists participated. The data were analysed using constant comparison method. Results: During the interview, many themes had emerged and some issues have been considered and some themes are either acceptable or unacceptable to be implemented in the framework. The findings are then categorized into three categorical themes: Current situation, contributing factors of unregistered drugs and solution. The findings had emerged two different pathways which are the themes that increased unregistered drugs and the themes that decreased unregistered drugs. Those themes are the perceptions from the pharmacist as respondents towards the unregistered drugs problem in Malaysia. Majority of them believed if there is the problem it must have the solution. Conclusion: As a conclusion, this study is to develop solutions and strategies in managing unregistered drugs in Malaysia by exploring practitioner (pharmacist) who practically with this issues and have experienced with consumers. The development of a problem-solving framework is useful and beneficial for future studies and the framework acts as a professional audit for comparison with the current situation and practice.
Keywords: Unregistered drugs; Problem-solving framework; Pharmacist; Perspectives; Malaysia